The Correlation between Serum Zinc Level and Liver Histology in Non-Alcoholic Steatohepatitis - Farid Kosari; Raika Jamali; Tayeb Ramim; Ebrahim Musavi Jahan Abad (Iranian Society of Pathology, 2019)
Background & Objective: The aim of this present study was to assess the relationship between serum zinc levels and liver histopathological findings in non-alcoholic steatohepatitis (NASH) patients.Methods: This case-control study was performed in consecutively selected NASH patients who had been referred to a general hospital. The control group consisted of age and sex-matched individuals with normal physical examinations, laboratory findings, and liver ultrasounds. Serum zinc level was measured using atomic absorption spectrophotometry. Liver histopathological findings were determined based on non-alcoholic fatty liver activity score.Results: A cohort of eighty biopsy-proven NASH patients and eighty controls were enrolled in the study. The mean serum zinc level was significantly lower in the NASH group compared with the controls. The mean serum zinc concentration was significantly lower in moderate and severe lobular inflammation groups than the mild group. After multiple adjustments for potential contributing variables, serum zinc level was associated with the severity of lobular inflammation. Nonetheless, it was not associated with liver steatosis and fibrosis. A serum zinc value of 89 (µg/dl) yielded a sensitivity and specificity of 93% and 86%, respectively, characterizing patients with lobular inflammation of less than two inflammatory foci per high-power field (HPF) from more advanced groups. Furthermore, a value of 79.55 (µg/dl) yielded a sensitivity and specificity of 87% and 100%, respectively, distinguishing those with a lobular inflammation grade of less than four foci per HPF from more advanced cases. Conclusion: Serum zinc level might be associated with the severity of lobular inflammation in NASH.